Analysis of Generation Z Parenting Styles and Children's Educational Awareness Using Decision Tree and K-Means Methods - Novi Syahfitri; Sudi Suryadi; Budianto Bangun; Angga Putra Juledi (SAINTIS Publishing, 2026)
This study analyzes how Generation Z parents' parenting styles and technology supervision influence children's educational awareness. The research applied a data mining approach within the Knowledge Discovery in Databases (KDD) framework using Decision Tree and K-Means algorithms. Data were collected through questionnaires from 10 parents in Sumberjo Village. The Decision Tree results show that technology use and supervision provide the highest information gain, indicating that they are the most influential factors in determining children's educational awareness. K-Means clustering with K = 3 also shows that groups characterized by better technology supervision and stronger parenting patterns tend to have higher educational awareness. Validation using RapidMiner produced results that were consistent with the manual calculations, confirming that the analytical model is valid for the dataset used in this study.